A Review of Caribbean Ecosytems and Fishery Resources Using ECOPATH Models - S.G. Smikle; V. Christensen; K.A. Aiken (Études Caribéennes)
This paper provides a review of ecosystems modelling within the Caribbean using the Ecopath approach and software tools. The review is not intended to provide a direct comparison of the modelled ecosystems attributes and performance, as this would require having access to the models and the data sets used to build the models. Rather, a general comparison is made of the outputs of the models and the various authors’ descriptions of ecosystem attributes.